Reelaborando conceitos e ressignificando a prática na educação infantil - Aguiar, Olivette Rufino Borges Prado (2006)
In this research we described the path of thirty one teachers involved with elementary school, amog which we included ourselves, looking for professional formation that allowed us to understand the function of educating childen. In this sense, this group of teachers begins a process of intentional, systematic and voluntary reflection, in an attempt to give new meanings to daily concepts of life and work, and linking them to their socialpractices. Having as reference the theoretical and methodological principles of socio-historical approach and collaborative research, the Group of Studies: The Dialogue Reflection as Re-meaning of Pedagogical Practice: a continuous education proposal, motivated by the willing and the necessity of re- elaborate knowledge about collaboration, reflection, infant education, playing and development which meets the new and goes the inverse way revisiting concepts and conception already consolidated, confronting and re-meaning them enlightened by one s own effort and the collaboration of pairs, mediated by Cycles of Reflexive Studies and Inter/intrapersonal Sessions. We can affirm that these tools helped the process of reflexivity put into practice by participants, which most important consequence was the theoretical re-meaning and practice in the ambit of infant education. During this investigation, we could see some theoretical and practice presuppositions which permitted to attribute to the exercise of reflexivity in collaboration the means into which the involved people could rescue the actions taken, justified their choices, confronted their theoretical options with their peers and with the systematized knowledge would question their certainties and rebuild in intra-psychological level, the knowledge elaborated socially. To this group which main activity is the docent profession, the personal and professional development constitutes the objective in which actions were articulated and operations which made learning possible as well as professional development